Evaluation of ameliorating effect of lycopene against testicular toxicity due to diethylnitrosamine using biochemical, spermatological and histopathological data - Kaya, Emre; Kaya, Seyma Ozer; Yilmaz, Seval; Ceribasi, Ali Osman; Turk, Gaffari (Wiley, 2019)
The aim of this study was to evaluate the possible therapeutic or protective effects of lycopene on diethylnitrosamine (DEN)-induced testicular lipid peroxidation and on the associated changes in spermatological parameters and histopathological architecture of rat testis. DEN is a carcinogenic substance that can be derived from chemicals used in agriculture, such as insecticides and nitrate. The rats were assigned to control, lycopene, DEN(1), DEN(2), lycopene + DEN(1), lycopene + DEN(2), DEN(1) + lycopene and DEN(2) + lycopene groups. During the study, lycopene was administered by oral gavage at a dose of 10 mg kg(-1) bw(-1) every other day for 10 days and DEN was administered at a dose of 200 mg kg(-1) bw(-1) as a single dose intraperitoneally. DEN was applied for 30 days in group DEN(1) and for 90 days in group DEN(2). Malondialdehyde (MDA) and reduced glutathione (GSH) levels, antioxidant enzymes activities, spermatological parameters, the weight of the reproductive organs (v. seminalis, prostate, testis and epididymis) and the histopathological structure were determined. MDA levels significantly increased, while GSH and antioxidant enzymes' activities decreased in DEN groups (p < 0.001). There was an increase in the rate of abnormal spermatozoa and a decrease in sperm density and motility, and reproductive organ weight (the weight of the right and left testis) in both DEN groups. Lycopene has normalised biochemical and spermatological parameters and reproductive organ weight. The histopathological examination of testicular tissue showed that the most significant histopathological change in DEN groups was the seminiferous tubule dilatation. These results suggest that besides the protective effects, the therapeutic effect of lycopene is possibly due to its antioxidant effects on DEN-induced testicular toxicity.
Keywords: antioxidant; diethylnitrosamine; lycopene; oxidative stress